Building Construction Permit Service at the Investment and One-Stop Integrated Service Office of Minahasa Regency - Marthinus Mandagi,; Thelma Wawointana,; Lendyane Tumewu, (Technium Social Sciences Journal, 2023)
The purpose of this study is to find out, analyze and describe how the Service Mechanism for Building Permits at the Investment Service and One-Stop Integrated Services in Minahasa Regency. The research method used is descriptive qualitative. with the results of research on the first indicator there are still many people who do not know the requirements that need to be input when registering. the second indicator is the location checking process is carried out to see whether the applicant's data matches the location or not and then there is a determination of retribution fees. third indicator the process and printing of Building Permit Decrees is still not effective in obtaining Building Permits. and on the fourth indicator the process of ratifying the SK IMB is often delayed because the officials and authorized officials are not in the office. Keywords, Services, Building Permits.